The given equation with t -1 is:
(t – 1)^3 + 6 (t – 1)^2 + 12 (t – 1) + 8
Expand each term before combining for easier visualization:
(t – 1)^3 = t^3 – 3 t^2 + 3t – 1
6 (t – 1)^2 = 6 t^2 – 12 t + 6
12 (t – 1) = 12 t - 12
Then substitute and combine:
-> t^3 – 3 t^2 + 3t – 1 + 6 t^2 – 12 t + 6 + 12 t – 12 + 8
t^3 + 3 t^2 + 3 t + 1 (ANSWER)
Answer:
27
Step-by-step explanation:
2, 7, 12, 17, 22, 27
Answer:
A. 24+24+120+160+200
Step-by-step explanation:
Surface area of the triangular prism= addition of the area of each shape that forms the prism
There are two triangles
Area of a triangle=1/2*base*height
=1/2*8*6
=1/2*48
=24
Area of two triangles=24+24
There are 3 rectangles with different dimensions
Back rectangle=length×width
=20×6
=120
Bottom rectangle=length ×width
=20x8
=160
Top rectangle=length × width
=20×10
=200
Surface area =Area of two triangles + Back rectangle + Bottom rectangle + Top rectangle
=24+24+120+160+200
Answer: 49°
Step-by-step explanation:
I'm guessing you meant complement? Complementary angles add up to 90°. 90° - 41° = 49°